1991
DOI: 10.1111/j.1558-5646.1991.tb04359.x
|View full text |Cite
|
Sign up to set email alerts
|

EVOLUTION OF PLUMAGE COLOR IN MALE PIED FLYCATCHERS (FICEDULA HYPOLEUCA): EVIDENCE FOR FEMALE MIMICRY

Abstract: Abstract.-We present the first evidence for sexual deception by female mimicry in birds. Using live, caged birds we show that territorial male pied flycatchers behave aggressively toward brightcolored males but display sexually toward female-like male intruders. We also show that the males that are fooled are those that lack recent sexual experience. All male pied flycatchers are dullcolored in winter. It is possible that young males are more constrained during the spring molt than older males since the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
3
26
1
Order By: Relevance
“…By maintaining low testosterone levels, or reducing testosterone levels, clean males may make themselves less threatening to the stained males. Subordinate male birds sometimes mimic female plumage or reduce badge size to be less threatening to territory-holding males (Rohwer et al, 1980;Slagsvold and Saetre, 1991). Similarly, unflanged male orangutans are tolerated by the flanged males (Utami Atmoko and van Hooff, 2004).…”
Section: Alternative Mating Tacticsmentioning
confidence: 97%
“…By maintaining low testosterone levels, or reducing testosterone levels, clean males may make themselves less threatening to the stained males. Subordinate male birds sometimes mimic female plumage or reduce badge size to be less threatening to territory-holding males (Rohwer et al, 1980;Slagsvold and Saetre, 1991). Similarly, unflanged male orangutans are tolerated by the flanged males (Utami Atmoko and van Hooff, 2004).…”
Section: Alternative Mating Tacticsmentioning
confidence: 97%
“…Another species in which the female‐mimicry hypothesis may be applicable is the pied flycatcher ( Ficedula hypoleuca ) as several studies of this species have shown that adult males have difficulty distinguishing between females and female‐like males (Slagsvold & Saetre, 1991; Saetre & Slagsvold, 1992, 1996; Saetre, 1993). Among the many studies of pied flycatchers (see Huhta & Alatalo, 1993), however, subadult males are not always treated like females.…”
Section: Hypothesized Benefits Of Subadult Plumagesmentioning
confidence: 99%
“…) and a white forehead patch (Potti & Montalvo ; Galván & Moreno ), in contrast to duller brown and white females. Males with more black feathers on the head, wings and back are more attractive to females in some populations (Slagsvold & Saetre ; Saetre et al. ; Galván & Moreno ), while larger forehead patches also seem to be preferred by females (Potti & Montalvo ; Dale et al.…”
Section: Introductionmentioning
confidence: 99%